High incidence of occult familial SDHD cases amongst Czech patients with head and neck paragangliomas - Guha, Anasuya; Vicha, Ales; Zelinka, Tomas; Kana, Martin; Musil, Zdenek; Pacak, Karel; Betka, Jan; Chovanec, Martin; Plzak, Jan; Boucek, Jan (Frontiers in Endocrinology, 2023)
Introduction: Head and neck paragangliomas (HNPGLs) are rare neuroendocrine tumors, which are mostly benign in nature. Amongst all genes, Succinate Dehydrogenase Subunit D (SDHD) is the most commonly mutated in familial HNPGLs. In about 30% of HNPGLs, germline mutations in SDHD can also occur in the absence of positive family history, thus giving rise to "occult familial" cases. Our aim was to evaluate the pattern of SDHD germline mutations in Czech patients with HNPGLs. Materials and Methods: We analyzed a total of 105 patients with HNPGLs from the Otorhinolaryngology departments of 2 tertiary centers between 2006 -2021. All underwent complex diagnostic work-up and were also consented for genetic analysis. Results: Eighty patients aged 13-76 years were included; around 60% with multiple PGLs were males. Carotid body tumor was the most frequently diagnosed tumor. Germline SDHD mutation was found in only 12% of the Czech patients; approximately 78% of those harboring the mutation had negative family history. The mutation traits had higher affiliation for multiple tumors with nearly 70% patients of ≤ 40 years of age. Conclusion: An SDHD mutation variant was shared amongst unrelated patients but no founder-effect was established. Our findings confirmed that the pattern of SDHD mutation distribution amongst HNPGLs in Czech Republic differs from most studies worldwide.